History in the Making A History of the People of the United States of America to 1877 - Locks, Catherine; Mergel, Sarah K.; Roseman, Pamela Thomas; Spike, Tamara (Open textbook library., 2013)
This textbook examines U.S. History from before European Contact through Reconstruction, while focusing on the people and their history.Prior to its publication, History in the Making underwent a rigorous double blind peer review, a process that involved over thirty scholars who reviewed the materially carefully, objectively, and candidly in order to ensure not only its scholarly integrity but also its high standard of quality.This book provides a strong emphasis on critical thinking about US History by providing several key features in each chapter. Learning Objectives at the beginning of each chapter help students to understand what they will learn in each chapter. Before You Move On sections at the end of each main section are designed to encourage students to reflect on important concepts and test their knowledge as they read. In addition, each chapter includes Critical Thinking Exercises that ask the student to deeply explore chapter content, Key Terms, and a Chronology of events.